Migration: A Response to the Transmigration program for Female Jamu Gendong Sellers - Sunaniah; Idham Irwansyah Idrus; Ulfa Utami Mappe (Journal of Social and Humanities, 2025)
Religion and culture dogma teaches that men have the responsibility an also the main role in the stability of the family economy. However, practically economic stability in each family cannot be separated from the women role, especially women who decided to work. In a patriarchy culture, women still occupy the subordinate position compared to men. Currently there are many women who participate in supporting the family economy. Even though they dared to take a double role in the family, in reality they remained in a limp position "the second livelihood seeker". The portraits of female sellers of "carried herbal" (jamu gendong) which support the family's economy and their efforts to still exist as traditional herbal medicine sellers in the midst of modern industrial competition are the focus of the study in this paper. The writing settings are displayed by seeing the woman selling herbal medicine as part of the overseas community. The aim of this study is to explore the life portrait of carried herbal sellers in overseas places. This study used qualitative methods with a phenomenological approach. The research location is in Pagar Alam village, Rt. 12 Rw. 04 Pagar Alam Utara District, South Sumatra Province. The data collection is done by primary data (observation, interviews) and secondary data (literature review). The research data were analyzed using Pierre Bourdieu's theory perspective with the concept of social capital, fields and habitus.